Disclaiming in the British Prime Minister Boris Johnson's Questions (PMQs) Sessions: A Pragmatic perspective - Fadhil, Eman Majeed; Dhayef , Qasim Abbas (Journal of Ecohumanism, 2024)
The study conducts disclaiming, which states that one has no responsibility for or knowledge of something that has occurred. Specifically, this research examines disclaiming language in spontaneous verbal interactions, particularly during Boris Johnson's Prime Minister's Questions sessions. The main goal of the study is to analyze the forms of disclaiming that Boris Johnson employed during these sessions and identifying the most common type. It also explores the pragmatic strategies employed in Boris Johnson's Prime Minister's Questions sessions. The research methodology involves presenting a theoretical overview of disclaimers alongside a comprehensive analysis of the chosen data using qualitative and quantitative methods. The research findings indicate that the representation of disclaimers in Boris Johnson's sessions relies fundamentally on three key types that frequently occur during these sessions. Furthermore, the study also highlights the pragmatic strategies that underpin the use of disclaimers, including speech acts, Grice’s conversational maxims, and politeness strategies. These findings emphasize the complex interplay between pragmatic strategies and the use of disclaiming in verbal interactions and highlight the importance of utilizing disclaiming in political discourse.